2018
DOI: 10.5530/pj.2018.4.105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Modulatory Effect of Combination of Spondias Pinnata and Whey Preparation on Intestinal Antioxidants and Inflammatory Markers in Etoposide Induced Rat Model for Mucositis

Abstract: Background:Etoposide is an important chemotherapeutic agent that is used to treat a wide spectrum of human cancers. The efficacy of this drug is often limited due to severe sideeffects such as mucositis, anorexia, myelosupperssion, alopecia. At present there are no anti-mucositic agents without side effects. To combat these side effects of cancer treatment, innovative and specific nutritional interventions are needed. The experimental procedure included an oral treatment with combination of Spondias pinnata an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…it has shown significant positive change with oral administration of Spondias pinnata bark extract. [2526] The current study with oral administration of AM fruit pulp in etoposide-induced rat showed significant rise in GSH levels. The GSH level was found drastically low in the rats which received etoposide alone when compared to normal controls.…”
Section: Discussionmentioning
confidence: 73%
“…it has shown significant positive change with oral administration of Spondias pinnata bark extract. [2526] The current study with oral administration of AM fruit pulp in etoposide-induced rat showed significant rise in GSH levels. The GSH level was found drastically low in the rats which received etoposide alone when compared to normal controls.…”
Section: Discussionmentioning
confidence: 73%